2002
DOI: 10.1074/jbc.m205109200
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Binding of the Catalytic Subunit of Protein Phosphatase 1 to the PKR Protein Kinase Is Necessary but Not Sufficient for Inactivation and Disruption of Enzyme Dimer Formation

Abstract: The PKR protein kinase is among the best-studied effectors of the host interferon (IFN)-induced antiviral and antiproliferative response system. In response to stress signals, including virus infection, the normally latent PKR becomes activated through autophosphorylation and dimerization and phosphorylates the eIF2␣ translation initiation factor subunit, leading to an inhibition of mRNA translation initiation. While numerous virally encoded or modulated proteins that bind and inhibit PKR during virus infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…One of these is protein kinase R, which is activated by autophosphorylation and dimerization following the binding of double-stranded RNA. Recently, it was reported that protein kinase R binds directly to PP1 and is dephosphorylated by associated PP1 (354). In accordance with protein kinase R being a physiological substrate of PP1, these investigators found that the activation of the kinase is prevented by the coexpression of PP1.…”
Section: Translationmentioning
confidence: 50%
“…One of these is protein kinase R, which is activated by autophosphorylation and dimerization following the binding of double-stranded RNA. Recently, it was reported that protein kinase R binds directly to PP1 and is dephosphorylated by associated PP1 (354). In accordance with protein kinase R being a physiological substrate of PP1, these investigators found that the activation of the kinase is prevented by the coexpression of PP1.…”
Section: Translationmentioning
confidence: 50%
“…This strategy also seems highly promising as a nontoxic modality for breast cancer treatment, because PKR in normal mammary epithelials remains bound to p58 inhibitor. Although we assessed only the p58 inhibitor of PKR in normal mammary and cancer cells, there are other intracellular regulators, some of which are heat shock proteins, mRNA of p23/TCTP, ribosome, p67, and protein phosphatase 1 (40)(41)(42)(43)(44). These intracellular regulators could also contribute to the decreased susceptibility of normal mammary epithelials to NO.…”
Section: Discussionmentioning
confidence: 99%
“…Leucine attenuated the increased phosphorylation of PKR by increasing expression of protein phosphatase 1 (PP1) (Fig. 5), which is known to dephosphorylate PKR (251). The decreased phosphorylation of PKR led to a decreased phosphorylation of eIF2␣, allowing conversion of eIF2.GDP to eIF2.GTP.…”
Section: A Control Of Protein Synthesis In Normal and Cachectic Statesmentioning
confidence: 99%